Analisis Faktor-Faktor yang Mempengaruhi Keberhasilan Rumah Makan dalam Menghadapi Persaingan di Desa Adat Legian - Ayu Ratna Dewisti; Made Ary Meitriana (Ekuitas: Jurnal Pendidikan Ekonomi, 2026)
The development of micro, small, and medium enterprises (MSMEs), particularly restaurants in Desa Adat Legian, Kuta District, Badung Regency—one of Bali’s main tourism destinations—has faced increasingly intense competition due to the growing number of business actors. This study aims to analyze the factors influencing restaurant success in coping with such competitive pressures. A descriptive quantitative approach was employed with a population of 63 restaurant units. Data were collected through interviews, questionnaires, and documentation, and analyzed using descriptive statistics, validity and reliability tests, as well as Exploratory Factor Analysis (EFA), preceded by the Kaiser-Meyer-Olkin (KMO) test and Bartlett’s Test of Sphericity. The results indicate that all research indicators were suitable for analysis and formed a single dominant, integrated factor comprising internal factors, external factors, customer-related factors, and the business environment. These findings confirm that restaurant success is not determined by a single variable, but rather by the synergy of effective business management strategies, adaptability to competitive dynamics, and a thorough understanding of customer needs in a sustainable manner.